Soil Organic Carbon Changes Impacted by Crop Rotational Diversity under No‐Till Farming in South Dakota, USA. Issue 4 (20th July 2017) - Alhameid, Abdullah; Ibrahim, Mostafa; Kumar, Sandeep; Sexton, Peter; Schumacher, T.E.
Abstract : Core Ideas: Diverse cropping with no‐till systems were compared with less diverse cropping systems. No‐till system with 4‐yr rotation improved soil organic carbon and soil physical properties. Long‐term application of 4‐yr rotation under no‐till system increased light fraction of carbon and nitrogen. Diverse cropping systems and no‐till (NT) are often suggested as management tools to improve soil organic carbon (SOC) and soil properties in fields with a history of intensive tillage. The present study was conducted to evaluate the interaction of tillage and rotation systems on SOC and selected soil properties. The long‐term site initiated at Beresford, South Dakota in 1991 is comprised of two tillage [NT and conventional‐till (CT)], and three crop rotations [maize ( Zea mays L.)–soybean ( Glycine max L.) (MS); maize–soybean–wheat ( Triticum aestivum L.) (MSW); and maize–soybean–wheat–oat ( Avena sativa L.) (MSWO)]. Soil sampling was conducted in the maize and soybean phases of each rotation in 2014. Soil samples were collected from four depths (0‐ to 7.5‐, 7.5‐ to 15‐, 15‐ to 30‐, and 30‐ to 60‐cm) after crop harvest, and analyzed for SOC, total nitrogen (TN), bulk density, water aggregate stability (1–2 mm), and light fractions of carbon and nitrogen. Data showed that after 23 years, the 4‐yr rotation significantly increased SOC concentrations up to 30‐cm in both tillage systems compared to that under 3‐ and 2‐yr rotations, which subsequently decreased bulk density in the 4‐yr rotation for these depths. There was also a significant interaction between tillage and rotation. The NT system significantly increased SOC relative to CT within the 4‐yr rotation in the top 30 cm. Data from this study revealed that long‐term use of diverse crop rotations (MSWO) under NT system in South Dakota, USA, improved SOC concentrations and other soil properties compared to that of less complex (MS) systems.